PENGARUH KINERJA KEPALA MADRASAH DAN KINERJA GURU TERHADAP MUTU LULUSAN SISWA MADRASAH ALIYAH DI KABUPATEN LAMPUNG TENGAH - Syarif Maulidin; Eti Hadiati; Nanang Supriadi (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
This research is motivated by the quality of SMA/MA level student graduates which is less than optimal, meaning that when viewed from the national exam scores they are not included in the top five highest score categories in Indonesia. Madrasa heads and teachers within the scope of educational institutions are the spearheads in creating the quality of graduates, so in this research these two factors will be tested for their influence on the quality of graduates. The method in this research is a quantitative approach with an ex-post facto type, with a population of all madrasa heads and teachers in Central Lampung district. Meanwhile, the samples were taken randomly from all madrasas. Data analysis techniques use simple and multiple regression tests with prerequisite tests for normality and linearity tests. From the results of this research, the author concludes: 1) There is a significant influence between the performance of madrasa heads on the quality of Madrasah Aliyah graduates in Central Lampung Regency which has a positive impact of 38.5%. 2) There is a significant influence between teacher performance on the quality of Madrasah Aliyah graduates in Central Lampung Regency which has a positive impact of 48.5%. 3) There is a significant influence between the performance of madrasah heads and teacher performance on the quality of Madrasah Aliyah graduates in Central Lampung Regency which has a positive impact of 75.6%.